2020
DOI: 10.1371/journal.pone.0237581
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal reflux, gastroesophageal reflux and dental disorders: A systematic review

Abstract: Objectives To investigate the role of gastroesophageal reflux disease (GERD) and laryngopharyngeal reflux (LPR) in the development of dental disorders. Methods The first outcome was review of the role of reflux in the development of dental disorders in adults. The second outcome was review of the potential pathophysiological mechanisms underlying the association between reflux and dental disorders. Three investigators screened publications for eligibility and exclusion based on predetermined criteria through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 66 publications
5
22
0
7
Order By: Relevance
“…RSS-12 and the identification of these oral and oropharyngeal findings may be both used in primary care medicine for the diagnosis and the evaluation of therapeutic response. The primary care physician has to be aware of the LPR signs and symptoms in children or adults with chronic dental disorders, i.e., decays or erosion, with regards to the potential association between LPR and these common conditions [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…RSS-12 and the identification of these oral and oropharyngeal findings may be both used in primary care medicine for the diagnosis and the evaluation of therapeutic response. The primary care physician has to be aware of the LPR signs and symptoms in children or adults with chronic dental disorders, i.e., decays or erosion, with regards to the potential association between LPR and these common conditions [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we observed that symptoms significantly improved or resolved with an adequate treatment and a long-term antireflux diet. A few studies investigated the involvement of reflux in dental lesions [ 17 ], or primary burning mouth syndrome [ 18 , 19 , 20 ], but authors reported conflicting results, which may be related to methodological discrepancies across studies [ 21 ]. Indeed, the majority of authors studied the association between burning mouth syndrome and reflux considering GERD and not LPR diagnostic criteria [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed that symptoms significantly improved or resolved with an adequate treatment and a long-term antireflux diet. A few studies investigated the involvement of reflux in dental lesions [18], or primary burning mouth syndrome [19][20][21] but authors reported conflicting results, which may be related to methodological discrepancies across studies [22]. Indeed, the majority of authors studied the association between burning mouth syndrome and reflux considering GERD and not LPR diagnostic criteria [19][20][21].…”
Section: Discussionmentioning
confidence: 99%